Comparative assessment of the awareness and utilization of government-initiated geriatric health and welfare schemes among the elderly population of urban and rural communities of western Maharashtra - Neha Kumari Verma; Soniya Saklani (International Journal Of Community Medicine And Public Health, 2026)
Background: India is experiencing a rapid demographic transition, leading to a growing elderly population with increasing health and social welfare needs. Although the Government of India and the Government of Maharashtra have introduced several geriatric health and welfare schemes, limited awareness and poor utilization continue to hinder their effective implementation. This study assessed and compared the awareness and utilization of government-initiated geriatric health and welfare schemes among elderly individuals residing in urban and rural communities of western Maharashtra and examined their association with selected socio-demographic variables. Methods: A descriptive comparative cross-sectional study was conducted over six weeks from October to November 2024 in selected urban and rural communities of western Maharashtra. A total of 200 elderly individuals (100 urban and 100 rural) were recruited using non-probability consecutive sampling. Data were collected using a validated structured interview schedule and analyzed using descriptive statistics, the Chi-square test, and the Mann-Whitney U test. Results: Rural participants demonstrated significantly higher awareness scores than urban participants (6.97±2.61 versus 5.41±2.15; Z=4.20, p